Discursos de docentes do Ciclo II: currículo oficial da secretaria da educação do município de São Paulo - Gomes, Anderson Severiano (Universidade Federal de São Carlos, 2022)
In 2017, the city of São Paulo updated – in a process of curricular reorientation – the City Curriculum, based on the National Common Curriculum Base (BNCC). The questions that drive this investigation are related to the questions: how do teachers in a multidimensional city like São Paulo, in disparate and complex territories, develop, or even recognize the Curriculum (which already has ready and established didactic material, with goals, evaluations, etc.)? Does this official curriculum meet teachers' expectations? What are your views on the changes implemented in the City Curriculum? Thus, the object of this study is related to the discourses of teachers, and the objective of this qualitative research is to analyze, under the Foucauldian perspective, how the discourses of teachers of Elementary School Final Years in the city of São Paulo, act on the official curriculum by implementing in 2017.As a methodological procedure, we intend to carry out an investigation of an exploratory nature, using methodological instruments such as: closed questionnaire - for an approximate universe of 100 teachers who work in the final years and from these results submit them to the IRaMuTeQ software (R Interface for Multidimensional Analysis of Texts and Questionnaires) with the purpose of starting a mapping of the statements and feeding the focal points of discussions; focus group with six teachers at each meeting (three meetings for each focus group); and, a focus group with semi-structured interviews with technicians from the Municipal Department of Education (SME/SP).The set of official discourses and teachers' discourse becomes curricular content and a logical aspect, and this junction builds the curriculum in public schools. As a result of this study, it is expected to know better the official curriculum implementing from 2017 the City of São Paulo; to go through the Foucaultian field on discourse analysis; identify if there is parrhesia and this we will identify as a gambiarra not in the pejorative sense linked to the term, but as innovation from the action of the teachers in performing their "courage in speaking truth", as their cunning and also if they announce forms of creation, resistance and otherness of teachers in the face of this curriculum, understanding the existing power relations, from their historical conception, to their effectiveness in practice, in the various territories of the city.
Cycle II teacher's speech: the official curriculum of the education department of the municipality of São Paulo
Keywords: Currículo Escolar; Currículo da cidade de São Paulo; discursos de professores; análise do discurso; gambiarra; School Curriculum; curriculum of the city of São Paulo; teacher´s speeches; speech analysis; gambiarra; CIENCIAS HUMANAS::EDUCACAO::CURRICULO